2022
DOI: 10.1177/00914150221143958
|View full text |Cite
|
Sign up to set email alerts
|

Sport Participation for Adults Aged 50 + Years: A Socioecological Analysis

Abstract: Sport participation can play a key role in older adults’ successful aging as it provides an enjoyable opportunity for leisure-time physical activity. Research focusing on the benefits of sport participation in later life and facilitators for involvement has been increasing in the past several years. Drawing on the socioecological model, this study investigated select socioecological factors that predict older adults’ sport participation from a holistic perspective. An online survey provided quantitative data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
(87 reference statements)
2
1
0
Order By: Relevance
“…In senior associations, the cost of the activities was also lower and, as Wong et al ( 51) also state, the financial insecurity that some groups experience in later life, for example women, can impact their ability to afford and access physical activities. Due to the results that men often participated in competitive sports than women are in line with what both Hirvensalo and Lintunen (52) and Chen et al (53) found. Playing competitive sport at younger age was a significant predictor of sport involvement during old adulthood (53).…”
Section: Results Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In senior associations, the cost of the activities was also lower and, as Wong et al ( 51) also state, the financial insecurity that some groups experience in later life, for example women, can impact their ability to afford and access physical activities. Due to the results that men often participated in competitive sports than women are in line with what both Hirvensalo and Lintunen (52) and Chen et al (53) found. Playing competitive sport at younger age was a significant predictor of sport involvement during old adulthood (53).…”
Section: Results Discussionsupporting
confidence: 88%
“…Due to the results that men often participated in competitive sports than women are in line with what both Hirvensalo and Lintunen (52) and Chen et al (53) found. Playing competitive sport at younger age was a significant predictor of sport involvement during old adulthood (53).…”
Section: Results Discussionsupporting
confidence: 88%
“…For instance, Engel and Nagel (2011) speculated that sports discontinuance might be influenced by life transitions such as childbirth and job changes but had no further verification. Similarly, Chen et al (2022) only discussed whether historical sports participation affected current participation, ignoring the specific roles of life transitions. Additionally, Deelen et al (2018) focused on youths aged 13–21 and found that players who changed schools had a higher probability of discontinuing tennis.…”
Section: Introductionmentioning
confidence: 99%